Beginning Hibernate for Hibernate 5 - Ottinger, Joseph B.; Linwood, Jeff; Minter, Dave (ITpro collection, 2016)
Get started with the Hibernate 5 persistence layer and gain a clear introduction to the current standard for object-relational persistence in Java. This updated edition includes the new Hibernate 5.0 framework as well as coverage of NoSQL, MongoDB, and other related technologies, ranging from applications to big data. Beginning Hibernate is ideal if you're experienced in Java with databases (the traditional, or connected, approach), but new to open-source, lightweight Hibernate. The book keeps its focus on Hibernate without wasting time on nonessential third-party tools, so you'll be able to immediately start building transaction-based engines and applications. Experienced authors Joseph Ottinger with Dave Minter and Jeff Linwood provide more in-depth examples than any other book for Hibernate beginners. They present their material in a lively, example-based manner--not a dry, theoretical, hard-to-read fashion. What You'll Learn " uild enterprise Java-based transaction-type applications that access complex data with " ibernate Work with Hibernate 5 using a present-day build process " se Java 8 features with Hibernate " ntegrate into the persistence life cycle " ap using Java's annotations " earch and query with the new version of Hibernate " ntegrate with MongoDB using NoSQL " eep track of versioned data with Hibernate Envers. Who This Book Is For Experienced Java developers interested in learning how to use and apply object-relational persistence in Java and who are new to the Hibernate persistence framework